2004
DOI: 10.1128/aem.70.12.7396-7403.2004
|View full text |Cite
|
Sign up to set email alerts
|

Integral Strategy for Evaluation of Fecal Indicator Performance in Bird-Influenced Saline Inland Waters

Abstract: Wild birds are an important nonpoint source of fecal contamination of surface waters, but their contribution to fecal pollution is mostly difficult to estimate. Thus, to evaluate the relation between feces production and input of fecal indicator bacteria (FIB) into aquatic environments by wild waterfowl, we introduced a new holistic approach for evaluating the performance of FIB in six shallow saline habitats. For this, we monitored bird abundance, fecal pellet production, and the abundance of FIB concomitantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The high correlation between the density of birds and the amount of Escherichia coli confirmed that bird droppings are scattered sources of fecal contamination in the inland water bodies (Kirschner et al 2004;Meerburg et al 2011). Meerburg et al (2011) showed that gull feces contain a higher average concentration of E. coli per gram than geese or coot feces.…”
Section: Discussionmentioning
confidence: 80%
“…The high correlation between the density of birds and the amount of Escherichia coli confirmed that bird droppings are scattered sources of fecal contamination in the inland water bodies (Kirschner et al 2004;Meerburg et al 2011). Meerburg et al (2011) showed that gull feces contain a higher average concentration of E. coli per gram than geese or coot feces.…”
Section: Discussionmentioning
confidence: 80%
“…The prevalence of microsporidiosis was statistically higher in waterfowl, and the aquatic status of an avian host was a predisposing factor for microsporidian infection. These findings are epidemiologically important, as most of the world's waterfowl species (i) are protected by environmental laws and occur in large numbers, (ii) have unlimited access to surface waters (including waters used for production of drinking water), and (iii) usually migrate quite long distances; in addition, most of the daily activity of these birds involves grazing in shallow waters, and the birds defecate into the water (24). It has been established by epidemiologists and the drinking water industry that the presence of aquatic birds in source water reservoirs is associated with declining water quality (1,9,18,24).…”
Section: Discussionmentioning
confidence: 99%
“…As waterfowl are an important source of pollution in beach areas (17,26) and can serve as potential reservoirs of human infections (13,36), the assays described herein would be useful in health risk-based analyses (i.e., epidemiological studies and quantitative microbial risk studies) of nonhuman fecal pollu- on May 7, 2018 by guest http://aem.asm.org/ tion in recreational waters. Additionally, having gull-specific markers in the fecal source-tracking toolbox will help beach managers better assess potential causes of beach postings beyond familiar fecal pollution sources such as municipal wastewater and therefore implement remediation practices that target the most relevant sources of pollution.…”
Section: Resultsmentioning
confidence: 99%